Associations of work stress with hair cortisol concentrations – initial findings from a prospective study. (March 2018) - Herr, Raphael M.; Almer, Christian; Loerbroks, Adrian; Barrech, Amira; Elfantel, Irina; Siegrist, Johannes; Gündel, Harald; Angerer, Peter; Li, Jian
Highlights: Findings on the relation of work stress with hair cortisol are mixed. Time-invariant aspects (like genetics factors) might blur results. We measured changes in work stress and hair cortisol between two time points. Results highlight a robust effect of work stress on hair cortisol. Abstract: There is ample evidence supporting the link between stress at the workplace and physical and mental health. One of the pathways potentially mediating those associations may involve the hypothalamic-pituitary-adrenal (HPA) axis, with cortisol as an end product. While theoretically plausible, findings on the association of self-reported work stress with hair cortisol concentrations (HCC) are inconclusive, being potentially biased by omitted pertinent factors. This issue can be addressed, among others, by eliminating time-invariant factors through consideration of variation within persons over time. To this end, the present study examined the association between variation in HCC and perceived work stress − as assessed by the Effort-Reward-Imbalance (ERI) model − between two points in time (t1 and t2) over one year in a sample of 40 male factory workers. Neither a cross-sectional association, nor a link between change in ERI and HCC levels at t2 was observed. There was however a robust association of the change in ERI with the change of HCC. This effect was independent of baseline HCC and other confounders (Beta = 0.414, S.E. = 0.155, p = 0.012). Accordingly, this is the first study revealing prospective evidence for the associations of work stress with HCC, while excluding potentially time-stable confounding factors, like genetic factors or phenotypic hair color.